Implementation, adoption and impact of clinical decision support system for antibiotic prescribing in primary care: a systematic review - Racha Ibrahim; Claire Durand; Monsey Macleod; François-Xavier Lescure; Claire Amaris Hobson; Esmita Charani; Gabriel Birgand; Raheelah Ahmad; Nathan Peiffer-Smadja (Journal of Antimicrobial Chemotherapy, 2026)
Abstract Background Clinical decision support systems (CDSS), computerized tools that assist clinicians in making guideline-based decisions, may support antimicrobial prescribing in primary care. Methods Studies on CDSS implementation, use and outcomes in primary care on PubMed/MEDLINE and Embase were included up to June 2025. Results Of the 64 full-text articles assessed, 40 were included. Most were multicentric (n = 33, 82.5%) and conducted in high-income countries (n = 33, 82.5%), and 19 were randomized controlled trials (47.5%). CDSS mainly targeted respiratory infections (n = 24, 60%) and were integrated into electronic health records in 24 studies (60%). Implementation strategies were assessed in 19 studies with almost all using a multimodal approach, most commonly involving modification of health record systems (n = 18, 45%) and audit and feedback (n = 17, 42.5%). Adoption was highly variable: among the 11 studies reporting use, CDSS were used in more than half of consultations in only five studies. Among the 32 studies assessing clinical outcomes, 17 reported reduced overall antibiotic prescribing. Barriers to CDSS use included perceptions of redundancy, time consumption, language limitations, alert fatigue, technical issues and concerns about negative impacts on patient–doctors trust. Conclusion CDSS may improve guideline-concordant antibiotic prescribing in primary care, but wide variability in implementation and real-world adoption limits generalizability and scalability